9th AIAA/CEAS Aeroacoustics Conference and Exhibit 2003
DOI: 10.2514/6.2003-3212
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Flowfield Analyses of Separate Flow Chevron Nozzles and Pylon Interaction

Abstract: A computational and experimental flow field analyses of separate flow chevron nozzles is presented. The goal of this study is to identify important flow physics and modeling issues required to provide highly accurate flow field data which will later serve as input to the Jet3D acoustic prediction code. Four configurations are considered: a baseline round nozzle with and without a pylon, and a chevron core nozzle with and without a pylon. The flow is simulated by solving the asymptotically steady, compressible,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 10 publications
6
46
0
Order By: Relevance
“…al. 5 ) and the acoustic effects reported here. The models corresponded to an approximate full scale to model scale factor of nine.…”
Section: Introductionsupporting
confidence: 65%
“…al. 5 ) and the acoustic effects reported here. The models corresponded to an approximate full scale to model scale factor of nine.…”
Section: Introductionsupporting
confidence: 65%
“…An initial Reynolds-averaged Navier-Stokes (RANS) computational fluid dynamics (CFD) study reported by Thomas et al 1 predicted mean and turbulent flow fields for various separate flow nozzle configurations including the pylon and core chevron nozzle. More recently, Massey et al 2 improved the computations by accounting for increased mixing due to high temperature gradients and showed excellent agreement with mean flow field measurements. These results have been used by Hunter et al 3 to predict the jet noise associated with these nozzle configurations using a 3-D noise prediction code called Jet3D.…”
Section: Introductionmentioning
confidence: 87%
“…A comparison of the mean axial velocity for the PIV measurements and rake measurements taken in the same facility 2 18 months prior to the PIV test is shown in Figure 7. Four different axial locations are shown.…”
Section: B Comparisons To Existing Datamentioning
confidence: 99%
See 1 more Smart Citation
“…NASA and industry had already developed considerable experience that gave NASA the confidence that this key assumption could be realized. This understanding had been developed through a series of extensive experimental and computational studies beginning in 2002 through 2005 on the fundamental effects of jet noise reduction and jet noise source re-distribution with chevron and pylon effects [3][4][5][6][7][8][9][10][11] . Building on this information by 2009, ERA had already developed a technical path for an HWB concept to reach the noise goal.…”
Section: Introductionmentioning
confidence: 99%